Perhitungan Nilai Ekonomi Total dalam Rangka Pemanfaatan Ruang Wilayah pulau Kalimantan - Djakapermana, Ruchyat Deni; Sitorus, Santun R.P.; Marimin, Marimin; Rustiadi, Ernan (Center for Research and Community Services ITB, 2005)
Total economic value is considered as a useful tool for analyzing objectively the change of economic level in certain area as a consequence of changing on the different policies of regional development based on regional spatial plan. Results calculation on the application of total economic value approach in Kalimantan region, shows that the total economic values calculated based on conservation scenario (Scenario A) and do nothing scenario (Scenario B) are about 2.065,22 trillion Rupiah, and 1.695,83 trillion Rupiah, respectively. The Benefit Cost Ratio (BCR) for scenario A (9,91) is higher than BCR for scenario B (3,44). This calculation gave an indication that comply with the previous premise that regional development in Kalimantan region should be based on regional spatial plan for Kalimantan region. Therefore, it is recommended that development control to make sure that developments comply with the regional spati al plan should be applied wisely and consistently.Keywords: Kalimantan spatial plan, total economic values, benefit-cost ratio